Biomarkers of fish consumption and risk of stroke or myocardial infarction - Wennberg, Maria (Yrkes- och miljömedicin, 2010)
The effect of fish consumption on the risk of cardiovascular disease has been extensively studied. Omega-3 fatty acids present in fish, namely eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), have been found to have beneficial effects through several mechanisms. In addition, selenium, an antioxidant, may be protective. Fish also represents the main human exposure source to the pollutant methylmercury (MeHg), which is associated with elevated cardiovascular risk in previous studies. The aim of this thesis was to evaluate whether MeHg is associated with the risk of myocardial infarction (MI) or stroke, whether EPA+DHA or selenium (Se) have protective associations, and if the overall association between fish consumption and risk of stroke or MI is detrimental or protective. A prospective incident case-control study design was used to study effects on stroke or MI. Three hundred and sixty-nine cases with twice as many matched controls were included in the study on stroke, while 431 cases with 499 controls participated in the MI study, all from the Northern Sweden Health and Disease Study. The data was collected from health examinations of the population from 1986 until 1999. Also, time trends in burdens of mercury (Hg), lead (Pb) and cadmium (Cd) in erythrocytes (Ery) from 1990 to 1999 were examined. The food frequency questionnaire (FFQ) used in the case-control studies was correlated with measurements of fatty acids in erythrocyte membranes as biomarkers of intake. In this northern Swedish population, levels of Ery-Hg and Ery-Pb decreased during the 1990´s, but Ery-Cd decreased only in smoking men. No significant associations were found between Ery-Hg or levels of EPA+DHA and the risk of stroke. Men reporting fish consumption >3 meals/week had an elevated risk of stroke. In the MI study, higher levels of Ery-Hg were associated with lower risk of MI. No clear associations were found for reported fish consumption, levels of EPA+DHA or Ery-Se. The validated FFQ has a fair reliability in estimating ...